Israel : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Israel. (IMF Staff Country Reports; Country Report ;, 2009)
The staff report for the 2008 Article IV Consultation of Israel on economic developments and policies is examined. Fiscal and monetary credentials have been established in markets. Banks and their supervisory arrangements have been robust, and growth has been strong, sustained, and balanced. Although public debt is much reduced, to about 80 percent of GDP, it remains vulnerable. Although domestic securities prices tracked those abroad downward, prompting outflows from provident funds, flows in domestic credit markets remained largely undisturbed.